Multi-objective optimization of a steering system considering steering modality. (December 2018) - Wang, ChunYan; Zhang, YuQi; Zhao, WanZhong
Highlights: This work introduces the steering modality into the study of the steering system researches the performances of steering. The natural frequency of steering system is obtained by Design of Experiments design method and response surface method. The multi-objective optimization is carried out by PSO and NSGA-II algorithm, respectively. Abstract: The steering modality and steering performance are coupled with each other. Thus, how to consider the influence of the steering modality on the steering performance and improve the system's overall performance is significant to the steering system. This work introduces the steering modality into the study of the steering system, and combines the dynamics model with the physical model to research the performance of steering feel, steering sensitivity and steering modality. Based on the dynamic model of the vehicle and steering system, the transfer functions of steering feel, steering sensitivity and steering stability are derived. Moreover, the natural frequency is obtained by combining of design of experiments (DOE) design method and response surface method. Then the optimization mathematical model of the steering system is established and the multi-objective optimization is carried out by particle swarm optimization (PSO) algorithm and non-dominated sorting genetic algorithm II (NSGA-II) respectively. The optimization results show that the steering system optimized by NSGA-II algorithm can better avoid the resonance with the engine at idle condition, and further improve the system's overall performances.